Tasco®, a Product of Ascophyllum nodosum, Imparts Thermal Stress Tolerance in Caenorhabditis elegans - Franklin Evans; Balakrishnan Prithiviraj; Alan T. Critchley; Wajahatullah Khan; Jatinder Singh Sangha; Di Fan; Saveetha Kandasamy (Marine Drugs, 2011)
Tasco®, a commercial product manufactured from the brown alga Ascophyllum nodosum, has been shown to impart thermal stress tolerance in animals. We investigated the physiological, biochemical and molecular bases of this induced thermal stress tolerance using the invertebrate animal model, Caenorhabiditis elegans. Tasco® water extract (TWE) at 300 µg/mL significantly enhanced thermal stress tolerance as well as extended the life span of C. elegans. The mean survival rate of the model animals under thermal stress (35 °C) treated with 300 µg/mL and 600 µg/mL TWE, respectively, was 68% and 71% higher than the control animals. However, the TWE treatments did not affect the nematode body length, fertility or the cellular localization of daf-16. On the contrary, TWE under thermal stress significantly increased the pharyngeal pumping rate in treated animals compared to the control. Treatment with TWE also showed differential protein expression profiles over control following 2D gel-electrophoresis analysis. Furthermore, TWE significantly altered the expression of at least 40 proteins under thermal stress; among these proteins 34 were up-regulated while six were down-regulated. Mass spectroscopy analysis of the proteins altered by TWE treatment revealed that these proteins were related to heat stress tolerance, energy metabolism and a muscle structure related protein. Among them heat shock proteins, superoxide dismutase, glutathione peroxidase, aldehyde dehydrogenase, saposin-like proteins 20, myosin regulatory light chain 1, cytochrome c oxidase RAS-like, GTP-binding protein RHO A, OS were significantly up-regulated, while eukaryotic translation initiation factor 5A-1 OS, 60S ribosomal protein L18 OS, peroxiredoxin protein 2 were down regulated by TWE treatment. These results were further validated by gene expression and reporter gene expression analyses. Overall results indicate that the water soluble components of Tasco® imparted thermal stress tolerance in the C. elegans by altering stress related biochemical pathways.